Effect of Ventilation Support on Oxidative Stress and Ischemia-Modified Albumin in Neonates - Dursun, Arzu; Okumuş, Nurullah; Erol, Sara; Bayrak, Tülin; Zenciroğlu, Ayşegül (American Journal of Perinatology, 2016)
Background and Objective Mechanical ventilation (MV) can induce oxidative stress, which plays a critical role in pulmonary injury in intubated neonates. Ischemia-modified albumin (IMA)—a variant of human serum albumin—is a novel biomarker of myocardial ischemia that occurs due to reactive oxygen species during ischemic insult. This study aimed to investigate IMA production due to oxidative stress induced during MV in neonates.Materials and Methods This study included 17 neonates that were ventilated using synchronized intermittent mechanical ventilation (SIMV; SIMV group) and 20 neonates ventilated using continuous positive airway pressure (CPAP; CPAP group). Blood samples were collected from each neonate during ventilation support and following cessation of ventilation support. Total antioxidant capacity (TAC) and total oxidant status (TOS) were measured using the Erel method. IMA was measured via an enzyme-linked immunosorbent assay kit (Cusabio Biotech Co., Ltd., Wuhan, China). The oxidant stress index (OSI) was calculated as OSI = TOS/TAC. Statistical analysis was performed using SPSS v.18.0 (SPSS Inc., Chicago, IL) for Windows.Results Among the neonates included in the study, mean gestational age was 34.7 ± 3.8 weeks, mean birth weight was 2,553 ± 904 g, and 54% were premature. There were not any significant differences in mean gestational age or birth weight between the SIMV and CPAP groups. Among the neonates in both the groups, mean IMA, TOS, and OSI levels were significantly higher during ventilation support (102.2 ± 9.3 IU mL–1, 15.5 ± 1.3 µmol H2O2 equivalent L–1, and 0.85 ± 0.22 arbitrary units [ABU], respectively), as compared with following cessation of ventilation support (82.9 ± 11.9 IU mL–1, 13.4 ± 1.3 µmol H2O2 equivalent L–1, and 0.64 ± 0.14 ABU, respectively) (p = 0.001). Among all the neonates in the study, mean TAC was significantly lower during ventilation support than the postventilation support (1.82 ± 0.28 mmol 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid [Trolox] equivalent L–1 vs. 2.16 ± 0.31 mmol Trolox equivalent L–1) (p = 0.001). There were no significant differences in mean TAC, OSI, or IMA levels between the SIMV and CPAP groups. The mean TOS level during ventilation support and the mean difference in TOS between during and postventilation support was significantly greater in the CPAP group than in the SIMV group. There were no significant relationships between the mean TOS, TAC, OSI, or IMA levels, and gestational age of the neonates.Conclusion SIMV and CPAP activated the oxidative stress and increased the IMA level in neonates; therefore, measurement of IMA and oxidant markers may be useful in the follow-up of lung injury in neonates due to ventilation support. Additional prospective studies are needed to compare the effects of various ventilation methods on oxidative stress and the IMA level in neonates.
Keywords: neonate; mechanical ventilation; total antioxidant capacity; total oxidant status; ischemia-modified albumin; IMA